Neoadjuvant therapy for resectable pancreatic ductal adenocarcinoma: The need for patient-centered research - Cloyd, Jordan M (World J Gastroenterol, 2020)
Pancreatic ductal adenocarcinoma is an aggressive cancer with high recurrence rates following surgical resection. While adjuvant chemotherapy improves survival, a significant proportion of patients are unable to initiate or complete all intended therapy following pancreatectomy due to postoperative complications or poor performance status. The administration of chemotherapy prior to surgical resection is an alternative strategy that ensures its early and near universal delivery as well as improves margin-negative resection rates and potentially improves long-term survival outcomes. Neoadjuvant therapy is increasingly being recommended to patients with pancreatic ductal adenocarcinoma, however, patient-centered research on its use is lacking. In this review, we highlight opportunities to focus research efforts in the domains of patient preferences, patient-reported outcomes, patient experience, and survivorship. Novel research in these areas may identify relevant barriers and facilitators to the use of neoadjuvant therapy thereby increasing its utilization, improve shared-decision making for patients and providers, and optimize the experience of those undergoing neoadjuvant therapy.